1966
DOI: 10.4319/lo.1966.11.2.0143
|View full text |Cite
|
Sign up to set email alerts
|

Primary Productivity in a Southern Great Plains Stream1

Abstract: Physico-chemical conditions and community metabolism in a relatively undisturbed stream in Oklahoma were studied from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
33
0

Year Published

1975
1975
2009
2009

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 9 publications
5
33
0
Order By: Relevance
“…Pronounced seasonal variations also occurred, although data were not tested for statistical significance, in the Raritan River, NJ (Flemer, 1970), Fort River, MA (Sumner & Fisher, 1979), River Arakawa, Japan (Tominaga & Ichimura, 1966), River Thames and River Kennet, England (Kowalczewski & Lack, 1971). However, seasonal differences in respiration in the Blue River, OK were not striking (Duffer & Dorris, 1966).…”
Section: Inter-biome Comparisonsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pronounced seasonal variations also occurred, although data were not tested for statistical significance, in the Raritan River, NJ (Flemer, 1970), Fort River, MA (Sumner & Fisher, 1979), River Arakawa, Japan (Tominaga & Ichimura, 1966), River Thames and River Kennet, England (Kowalczewski & Lack, 1971). However, seasonal differences in respiration in the Blue River, OK were not striking (Duffer & Dorris, 1966).…”
Section: Inter-biome Comparisonsmentioning
confidence: 99%
“…For example, the metabolism of stream communities has been measured using gas changes in chambers for partial day (McConnell & Sigler, 1959;Bombowna, 1972;Marker, 1976b;Sumner& Fisher, 1979) or entire day incubations (Pennak & Lavelle, 1979;Naiman, 1983). Open system gas techniques were employed to estimate annual metabolism for a single reach (Odum, 1957;Hall, 1972;Fisher & Carpenter, 1976;Simonsen & Harremoes, 1978;Cushing& Wolf, 1982), to derive single season data for several river reaches (H oskin, 1959;Wright & Mills, 1967;Hornberger et al, 1977), and in two instances to measure metabolism in more than one reach at several times of year (Duffer & Dorris, 1966;Flemer, 1970). Isotopic procedures also have been employed to estimate periphytic (Elwood & Nelson, 1972;Naiman, 1976;Bott & Ritter, 1981;Hornick et al, 1981) and planktonic (Wissmar et al, 1981) …”
mentioning
confidence: 99%
“…There is little doubt that large stones have a well established flora, whilst small ones may be so moved during periods of high flow that the flora is reduced (Duffer & Dorris, 1966;Marker & Willoughby, 1988) and at the time of sampling the flora may be in a stage of progression towards a more stable community; small stones may in fact never reach the same floral composition as large. The effect of position in the stream (marginal or nearer the centre) may affect the flora; the orientation of the surface of the stone (facing upstream or downstream) does affect the composition of the flora (Cazaubon & Loudiki, 1986;Stevenson, 1983;Stevenson et al, 1985;Snoejis, 1988).…”
Section: Choice Of Methodsmentioning
confidence: 99%
“…Huda et al [79] in their study in rice-fields of Bangladesh reported the periphyton based aquaculture as economically viable technology for increasing fish production with cheaper local resources. Duffer and Dorris [80] suggested that the substrate type rather than light intensity or nutrient was the effective agent in periphyton based system. When compared to artificial substrates, studies revealed that periphyton develops better on natural substrate due to its differences in the hydrophilic characteristics [81].…”
Section: Self-substrating To Rice-fish Culturementioning
confidence: 99%